The association between financial performance and occupational injuries/diseases in workplaces of South Korea: interpretation based on managerial characteristics of workplaces - Jinyoung Moon; Atsuko Ikeda-Araki; Yongseok Mun (European Journal of Medical Research)
Abstract Introduction This study investigated the association between the financial performance of workplaces and the incidence of occupational injuries and diseases using the Workplace Panel Survey, a workplace-related national statistical survey in South Korea. Methods The dependent variables were those related to the incidence of occupational injuries and diseases. The independent variables were those related to the financial performance of each workplace. Multilevel Poisson regression (or logistic regression) and linear regression analyses were used. Results For the number of victims, the average number of workers, interest income, interest expenses, and value-added per person were associated with a significantly increased relative risk (RR). In contrast, lease expense2, depreciation and amortization, and initial/ending industrial property rights were associated with a significant decrease in RR. For the existence of occupational injuries/diseases, taxes and duties1, and welfare/benefits expenses were associated with a significant increase in the odds ratio (OR). In contrast, severance pay2, depreciation/amortization, and average number of workers were associated with a significant decrease in OR. Discussion As the financial status of workplaces worsened, the incidence of occupational injuries and diseases increased. In contrast, as the operating profit and amount of tangible assets (subject to depreciation and amortization) of workplaces increased, the incidence of occupational injuries and diseases decreased. As the number of workers increased, the number of occupational injuries and diseases also increased; however, the odds of occupational injury or disease decreased. The decreasing number of occupationally injured or diseased workers, along with the increasing number of transport devices, might have resulted from special consignment subcontracts between cargo truck owners and shipping companies in South Korea.